Does the BI 7 Days (Reverse) Repo Rate and Exchange Rate Affect Liquidity With Inflation as Intervening Variables on Islamic Commercial Banks in Indonesia? - Zahra, Qiny Shonia Az; Masrifa, Dina; Marliana, Nissa Ayu (JURNAL EKONOMI SYARIAH, 2023)
Introduction to The Problem: According to Islamic commercial bank liquidity data for the last 5 years, Islamic commercial bank liquidity has fluctuated but tends to decrease. the liquidity crisis that occurred in banks causing banks to default on most of their obligations. In the new normal era, Islamic banking liquidity is still faced with challenges and opportunities that need to be considered by Islamic banking industry.Purpose/Objective Study: The purpose of this study is to analyze macroeconomic factors, namely the BI 7 Days (Reverse) Repo Rate and Exchange Rate which affects the Liquidity of Islamic Commercial Banks with Inflation as an intervening variable.Design/Methodology/Approach: This type of research is quantitative research with secondary data of the type of time series data, monthly data from BIDRR, Exchange Rates, Inflation, and Liquidity of Islamic Commercial Banks for five years, namely 2017-2022. The sample used is purposive sampling. The data analysis technique in this study is Partial Least Squares-Structural Equation Model (PLS-SEM).Findings: Based on the results of path analysis both directly and indirectly, this study indicates that variable BI 7 Days Reverse Repo Rate and Exchange rate effect significant to the Liquidity of Islamic Commercial Banks with Inflation as an Intervening Variable, either directly or indirectly.Paper Type: Research Article